plz answer these question....
Attachments:
![](https://hi-static.z-dn.net/files/d34/04d3e2622a53f441c3f53c0491479fc3.jpg)
Answers
Answered by
1
put value @(x+1) => (x = -1)in the equation , if it comes zero then it is the factor of that equation.
Answered by
0
Answer:
yes x+1 is a factor of x^3+3x^2+3x+1
Step-by-step explanation:
p(x) = x^3+3x^2+3x+1
x+1=0
then x=-1
p(-1)=0
(-1^3)+3(-1^2)+3(-1)+1
-1+3+(-3)+1
=0
p(-1)=0
then x+1 is a factor of x^3+3x^2+3x+1
Similar questions
Math,
5 months ago
Hindi,
5 months ago
English,
5 months ago
Environmental Sciences,
11 months ago
Hindi,
11 months ago
Social Sciences,
1 year ago
Biology,
1 year ago